An Experience in Establishing the Mangrove Reference Data Center (MRDC) and its Augmented Reality Based Application - Syafiq Alam Shah, Mohd; Azam Osman, Mohd; Zawawi Talib, Abdullah; Azizah Mohd Nor, Siti (International Journal of Engineering and Technology, 2018)
Mangrove forest is an ecosystem that is highly diverse not only in mangrove plants but also supports rich assemblages of fauna and other non-mangrove floral species.Â It provides numerous kinds of ecosystem services that are of great benefit to humankind. However, to the general public, knowledge on the importance of mangrove ecosystems is very limited. In this paper, we present our experience in establishing the Mangrove Reference Data Center (MRDC) and its augmented reality-based mobile application called Kilim Scouter which provides information details of mangrove plants and related information to the users. MRDC is a data center that stores information details of mangrove plants in Kilim Geoforest Park in Langkawi Island, Malaysia such as common and scientific names of species, as well as its distribution (GPS location).Â In addition, MRDC also stores other information for example other inhabitants of the ecosystem and non-living entities such as Karstic hills and caves found in the Mangrove ecosystem. MRDC comes with a web application that acts as an interface to MRDC for accessing, adding or modifying the information details of mangrove plants. Kilim Scouter is a mobile application which deploys Augmented Reality (AR) technology, a technology through which the view of the real world environment is augmented by adding computer-generated elements/objects. Kilim Scouter utilizes the AR technology to automatically track and identify the mangrove plants and its related information, and then provides the information by retrieving data from MRDC. MRDC and Kilim Scouter are capable of providing on-the-go accessibility of information details of mangrove plants and target users such as tourists and researchers. This application will create awareness on the importance of the mangrove ecosystems and thus, assist the effort in sustaining the mangrove ecosystem.Â Â